2021
DOI: 10.1001/jama.2020.25864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Discontinuing vs Continuing Angiotensin-Converting Enzyme Inhibitors and Angiotensin II Receptor Blockers on Days Alive and Out of the Hospital in Patients Admitted With COVID-19

Abstract: It is unknown whether angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) have a positive, neutral, or negative effect on clinical outcomes in patients with coronavirus disease 2019 (COVID-19).OBJECTIVE To determine whether discontinuation compared with continuation of ACEIs or ARBs changed the number of days alive and out of the hospital through 30 days. DESIGN, SETTING, AND PARTICIPANTSA randomized clinical trial of 659 patients hospitalized in Brazil with mild to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
312
2
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(361 citation statements)
references
References 43 publications
16
312
2
13
Order By: Relevance
“…Recently, the results from two randomized clinical trials in which regular users of RASIs who were admitted to hospital for COVID-19 were assigned to discontinuation or continuation arms, have been reported (BRACE-CORONA [18] and REPLACE COVID [19] trials) and both found no difference in the mortality rates, supporting our results.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, the results from two randomized clinical trials in which regular users of RASIs who were admitted to hospital for COVID-19 were assigned to discontinuation or continuation arms, have been reported (BRACE-CORONA [18] and REPLACE COVID [19] trials) and both found no difference in the mortality rates, supporting our results.…”
Section: Discussionsupporting
confidence: 88%
“…While most studies have reported no association between the use of ACEI or ARB and the occurrence of COVID-19 [16][17][18][19][20][21][22][23][24][25], we found that the presence of a claim record of an ACEI prescription was associated with an 8% reduction in the OR of a COVID-19 infection. While this finding warrants further investigation, we do not believe it justifies a change in clinical practice.…”
Section: Plos Onecontrasting
confidence: 82%
“…patients in France [21], 1,603 patients in Italy [22], 338 patients in Saudi Arabia [23], 659 patients in Brazil [24], and 1,449 patients in the US [25] revealed no significant associations. Our study design allowed us to differentiate ACEI use from ARB use by utilizing claims data from Veterans with prescriptions for ACEI only, for ARB only, or for either ACEI or ARB, compared to Veterans with prescriptions for neither ACEI nor ARB.…”
Section: Plos Onementioning
confidence: 88%
“…Исследование REPLACE COVID проводилось в 20 крупных больницах в семи странах мира с участием 152 пациентов (средний возраст 62 года), которые перед госпитализацией с COVID-19 получали ИАПФ или БРА II [60]. В группах больных, рандомизированных для продолжения (n = 75) или прекращения приема ИАПФ или БРА II (n = 77) не наблюдалось существенных различий среднего глобального рейтинга (первичная конечная точкавремя до наступления смерти, продолжительность искусственной вентиляции легких, время на заместительной почечной терапии или вазопрессорной терапии, а также полиорганной дисфункции в период госпитализации) -73 против 81 соответственно.…”
Section: применение блокаторов раас при известном или предполагаемом Covid-19unclassified